AKLIMATISASI ANGGREK HITAM (Coelogyne pandurata Lindl.) HASIL PERBANYAKAN IN VITRO PADA MEDIA BERBEDA - Ayu Purnama Adi, Ni Kade; Astarini, Ida Ayu; Adriani Astiti, Ni Putu (SIMBIOSIS; Vol 2 No 2 (2014))
Black orchid (Coelogyne pandurata Lindl.) is an orchid endemic to the island of Borneo. However, its existence is increasingly threatened with extinction. Conventional propagation efforts require a long time. Therefore in vitro propagation was performed. The purpose of this study was to determine the growth response of black orchids on the media and different planting techniques. Black orchid plantlets that have been sub-cultured was acclimatized in four different media types ie moss, fern, wood charcoal, wood charcoal and coconut fiber mixture and different planting techniques namely compot (community pot) and the individual, were allowed to grow for three months. Randomized block design (RBD) was utilised, obtained 8 combination treatments, with 7 replicates. The results showed black orchid has a good growth response in the media moss, ferns, and a mixture of wood charcoal and coconut fiber, while the wood charcoal media showed unfavorable results. Different planting techniques showed no significant results. Percentage of high life shown in mixed media wood charcoal and coconut fiber and compot techniques. Keyword : Black orchid (Coelogyne pandurata Lindl.), acclimatization, media